Tree-year period evolution of the nutritional condition of children with mielomeningocelis - Müller Coelho, Cynthia; Célia da Silva, Regina; Miyeko Egashira, Elizabeth; Lima Ribeiro, Sandra Maria (O Mundo da Saúde, 2009)
This paper aims to describe and classify longitudinally the anthropometric profile of a group of children with mielomeningocelis included in a special program of physical activities. Twenty and four children with mielomeningocelis were evaluated at three moments with an interval of 1 year. Factors evaluated were weight, stature and Body Mass Index (BMI). Children were classified in accordance to the percentile of stature/age (S/A) and BMI/age (IMC/idade) correlations. From the total of evaluated children, 54,2% (n = 13) were of male (age: 7,0 ± 2.4 years) and 45.8% (n = 11) female (age 6,0 ± 2.0 years). The main findings were: most children had a growth deficit that was not reversed in a three-year interval; most children tend to become overweight and/or obese, something slightly attenuated in boys and slightly aggravated in girls. It was possible to observe nutritional deviations in this group of children (low stature, overweight and obesity), and the maintenance of these during a period of three years. Considering this, some recommendations may be made: one should consider the possibility of developing specific growth curves for this type of compromising, the accomplishment of studies comparing physically active and sedentary children, submitted or not to nutritional guiding.